IMPROVING STUDENTS' UNDERSTANDING OF ECOSYSTEMS THROUGH LEARNING MEDIA IN ELEMENTARY SCHOOLS - Ida fazilla; Siti Mayang Sari; Akmaluddin; Fitriani Manurung (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This descriptive qualitative research is an elaboration of the material developed through students' understanding through learning media.A deep understanding of ecosystems is essential for creating awareness of the need to protect the natural environment for the sustainability of our planet. This study uses an experimental approach involving elementary grade students as research subjects. An interactive and engaging learning media specifically designed to describe various aspects of ecosystems, including biotic and abiotic components, food chains, water cycles, and interactions between organisms. The use of interactive educational technology is expected to facilitate a more effective and enjoyable learning process. This research was conducted within a certain period of time by measuring the level of students' initial understanding of the ecosystem before the instructional media intervention and then compared with the level of understanding after the learning process using the media. In addition, comparisons were also made between groups of students who used learning media and groups of students who studied through conventional methods.